2008
DOI: 10.4148/2378-5977.1520
|View full text |Cite
|
Sign up to set email alerts
|

Substituting steam-flaked corn with distiller’s grains alters ruminal fermentation and diet digestibility (2008)

Abstract: Rapid expansion of fuel ethanol production in the High Plains, where feedlots commonly use steamflaked corn diets, has popularized substituting dried distiller's grains with solubles (DDGS) for a portion of the steam-flaked corn. Most of the starch in corn is removed during ethanol production. The residual material is rich in fiber, ruminal undegradable protein, and fat. Adding roughage to high-concentrate finishing diets helps maintain ruminal function by stimulating salivation, rumination, and gut motility. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In the present study, steers fed D-10S had numerically fewer bouts of SARA and ARA compared with steers fed CON, and tended to have smaller AUC below pH 5.2 compared with CON, observations that support our hypothesis. However, changes in ruminal pH as a result of the inclusion of DDGS in the diet can be confounded by increases in total DMI (Klopfenstein et al, 2008;Uwituze et al, 2008;Corrigan et al, 2009). Corrigan et al (2009) reported decreased mean ruminal pH and greater AUC below pH 5.6 and 5.3 when corn wet distillers grains with solubles (WDGS) replaced 40% of the dietary DM of either dry-rolled corn, high-moisture corn, or steam-flaked corn.…”
Section: Ruminal Ph Response To Ddgs Inclusionmentioning
confidence: 99%
“…In the present study, steers fed D-10S had numerically fewer bouts of SARA and ARA compared with steers fed CON, and tended to have smaller AUC below pH 5.2 compared with CON, observations that support our hypothesis. However, changes in ruminal pH as a result of the inclusion of DDGS in the diet can be confounded by increases in total DMI (Klopfenstein et al, 2008;Uwituze et al, 2008;Corrigan et al, 2009). Corrigan et al (2009) reported decreased mean ruminal pH and greater AUC below pH 5.6 and 5.3 when corn wet distillers grains with solubles (WDGS) replaced 40% of the dietary DM of either dry-rolled corn, high-moisture corn, or steam-flaked corn.…”
Section: Ruminal Ph Response To Ddgs Inclusionmentioning
confidence: 99%